Roles of MMP-2 and MMP-9 and their associated molecules in the pathogenesis of keloids: a comprehensive review - Wang, Yajie; Zheng, Liying; Zhang, Lai; Tai, Yuncheng; Lin, Xuesong; Cai, Zhencheng (Frontiers in Pharmacology, 2024)
Keloid scars (keloids), a classical type of abnormal scar tissue formation, remain a therapeutic challenge in the field of dermatology and plastic surgery due to the unsatisfactory treatment outcomes. Keloid scars (keloids), a prototypical form of aberrant scar tissue formation, continue to pose a significant therapeutic challenge within dermatology and plastic surgery due to suboptimal treatment outcomes.Gelatinases are a subgroup of matrix metalloproteinases (MMPs), a family of enzymes that play an important role in the degradation and remodeling of the ECM (a pivotal factor for keloids development). Gelatinases include gelatinase A (MMP-2) and gelatinase B (MMP-9). Since accumulating evidence has shown that gelatinases played a crucial role in the process of keloid formation, we summarized the current knowledge on the association between MMP-2 and MMP-9 expression and the pathological process of keloids through a comprehensive review. This review demonstrated that the interplay between MMP-2, MMP-9, and their regulators, such as TGF-β1/Smad, PI3K/AKT, and LncRNA-ZNF252P-AS1/miR-15b-5p/BTF3 signaling cascades, involved in the intricate balance governing ECM homeostasis, collectively driving the excessive collagen deposition and altered tissue architecture observed in keloids. In summary, this review consolidates the current understanding of MMP-2 and MMP-9 in keloid pathogenesis, shedding light on their intricate involvement in the dysregulated keloids processes. The potential for targeted therapeutic interventions offers presents promising avenues opportunities for advancing keloid management strategies.